Penerapan Slow Stroke Back Massage (SSBM) untuk Menurunkan Kecemasan pada Lansia Hipertensi di RSD K.R.M.T. Wongsonegoro Semarang - Sylvana Yasika Priyatna; Amrih Widiati (USADA NUSANTARA : Jurnal Kesehatan Tradisional, 2026)
Advancing age leads to a decline in cardiovascular function, which contributes to the high prevalence of hypertension among the elderly; this condition is often accompanied by psychological issues such as anxiety. Unmanaged anxiety can activate the sympathetic nervous system and trigger vasoconstriction of blood vessels, thereby exacerbating hypertension. This descriptive case study aims to examine the application of Slow Stroke Back Massage (SSBM) therapy in reducing anxiety among older adults with hypertension in Room Sadewa 2 at K.R.M.T. Wongsonegoro General Hospital in Semarang. SSBM was applied as a non-pharmacological intervention involving cutaneous stimulation to promote the production of endorphins and serotonin. The results of the case study showed a significant reduction in anxiety levels after three sessions of SSBM therapy, followed by the relief of muscle tension, improved sleep patterns, and the achievement of hemodynamic stability in the patients. Based on these results, it can be concluded that the application of SSBM therapy is effective in reducing anxiety levels while helping to stabilize blood pressure in elderly patients with hypertension. This cutaneous stimulation therapy is recommended for routine implementation by nursing staff as part of comprehensive, humanistic, and self-directed nursing care, both in a hospital setting and as a form of self-care at home.